Experimental and theoretical study of tracer diffusion in a series of (CoCrFeMn)100−xNix alloys. (1st August 2020) - Kottke, Josua; Utt, Daniel; Laurent-Brocq, Mathilde; Fareed, Adnan; Gaertner, Daniel; Perrière, Loïc; Rogal, Łukasz; Stukowski, Alexander; Albe, Karsten; Divinski, Sergiy V.; Wilde, Gerhard
Graphical abstract: Abstract: Tracer diffusion of all constituting elements is studied at various temperatures in a series of (CoCrFeMn) 100 − x Ni x alloys with compositions ranging from pure Ni to the equiatomic CoCrFeMnNi high-entropy alloy. At a given homologous temperature, the measured tracer diffusion coefficients change non-monotonically along the transition from pure Ni to the concentrated alloys and finally to the equiatomic CoCrFeMnNi alloy. This is explained by atomistic Monte-Carlo simulations based on a modified embedded-atom potentials, which reveal that local heterogeneities of the atomic configurations around a vacancy cause correlation effects and induce significant deviations from predictions of the random alloy model.